Inside Back Cover: Elucidation of the CO‐Release Kinetics of CORM‐A1 by Means of Vibrational Spectroscopy (ChemPhysChem 7/2016). Issue 7 (4th March 2016) - Klein, Moritz; Neugebauer, Ute; Schmitt, Michael; Popp, Jürgen
Abstract : IR absorption spectroscopy is applied to observe the gas phase above decaying, pH‐buffered solutions of Na2 [H3 BCOO] (CORM‐A1). H3 BCO was detected as intermediate and a pseudo‐consecutive first‐order reaction with the rates k 1 and k 2 was found." More information can be found in the Full Paper by J. Popp et al. onpage 985 in Issue 7, 2016 (DOI:10.1002/cphc.201501062 ).